Peran Orang Tua Dalam Memberikan Pendidikan Iman dan Seni Bagi Anak Penyandang Disabilitas Down Syndrome - Nasaruddin Nasaruddin (Masokan: Ilmu Sosial dan Pendidikan, 2022)
Abstract : Special education for people with Down syndrome should receive care in various patterns, one of which is through religious and artistic education. The planting of creative arts education should still be given by parents, in order to be able to continue to build commitment in increasing the joy of learning in children with DS. Parents play an important role in maintaining and educating children with Down syndrome, to avoid various kinds of influences on children's growth and mental development due to the limited thinking of children with Down syndrome. This article provides a new understanding for parents in shaping the pattern of presenting creative arts education in the selection of schools with special needs in various ways to carry out their duties and responsibilities as parents. The method used in this study uses a qualitative descriptive method by taking an emic perspective approach to parents who have children with DS. This study intends to explain how the lives of parents in providing creative art parenting to children with Down syndrome in the face of stigma in society to parents that DS children are special children by increasing the involvement of researchers directly and deeply.  Keywords: Disability, Parents, faith and art education, positive thinking.     Abstrak: Pendidikan khusus bagi penyandang down syndrome harus mendapat perhatian dalam berbagai pola, salah satunya melalui pendidikan agama dan seni. Penanaman pendidikan seni kreatif tetap harus diberikan oleh orang tua, agar dapat terus membangun komitmen dalam meningkatkan keceriaan belajar pada anak DS. Orang tua berperan penting dalam menjaga dan mendidik anak down syndrome, untuk menghindari berbagai macam pengaruh terhadap tumbuh kembang anak akibat keterbatasan pemikiran anak down syndrome. Artikel ini memberikan pemahaman baru bagi orang tua dalam membentuk pola penyajian pendidikan seni kreatif dalam pemilihan sekolah berkebutuhan khusus dalam berbagai cara dalam menjalankan tugas dan tanggung jawabnya sebagai orang tua. Metode yang digunakan dalam penelitian ini menggunakan metode deskriptif kualitatif dengan mengambil pendekatan perspektif emic pada orang tua yang memiliki anak DS. Penelitian ini bermaksud menjelaskan bagaimana kehidupan orang tua dalam memberikan seni kreatif parenting pada anak down syndrome dalam menghadapi stigma di masyarakat kepada orang tua bahwa anak DS adalah anak istimewa dengan meningkatkan keterlibatan peneliti secara langsung dan mendalam. Kata kunci: Disabilitas, Orang tua, pendidikan iman dan seni, berpikir positif.